Anti-inflammatory Effect of Trigona spp. Propolis in Restricting Edema Volume - Wulantika Nurhayati; Vycke Yunivita Kusumah Dewi; Teguh Marfen Djajakusumah (Faculty of Medicine Universitas Padjadjaran, 2015)
Background: Inflammation is a normal response that potentially harmful if it is uncontrolled. On the other hand, it is necessary to find an alternative anti-inflammatory as most anti-inflammatory drugs available nowadays still have adverse effects. Trigona spp. propolis is one of the potential anti-inflammatory alternatives because of its flavonoid, especially caffeic acid phenethyl ester, which is known as an active compound in anti-inflammatory process. This study aimed to understand the anti-inflammatory effect of Trigona spp. prolisin reducing edema volume in rat’s paw.Methods: An experimental study was performed on 20 male wistar rats. The rats were divided into control and experimental groups with 10 rats in each group. Control group was treated by propylene glycol 1 ml/day and experimental group was treated by Trigona spp. propolis 200 mg/kg body weight/day. The inflammation was induced by subcutaneous injection of λ-carrageenan 1% at plantar one hour after the treatment. Edema volumes were measured by plethysmometer every hour at 1 to 6 hours and once at 24 hours after induction. The difference in edema volumes was calculated in percentage. This study was conducted during October 2012 at the Pharmacology and Therapy Laboratory, Faculty of Medicine, Universitas Padjadjaran Bandung.Results: The increase of edema volume (in percentage) in control group and Trigona spp. propolis treated group are 100.64±32.22 and 56.46±20.38 respectively (p value=0.000). Multiple comparisons using Dunnet and Duncan post hoc test showed significant differences that were observed at 3, 4, 5, and 6 hours after inflammatory induction.Conclusion: Trigona spp. propolis has an anti-inflammatory effect in reducing edema volume in rat’s paw. The most significant effect was observed at 3, 4, 5, and 6 hours after inflammatory induction. Trigona spp. propolis might have a potential to be developed as a future anti-inflammatory drug.Keywords: Edema volume, inflammation, propylene glycol, Trigona spp, propolisDOI: 10.15850/amj.v2n1.440